ChemInform Abstract: Catalytic Dehydrogenative Si—N Coupling of Pyrroles, Indoles, Carbazoles as well as Anilines with Hydrosilanes Without Added Base. Issue 25 (3rd June 2013) - Koenigs, C. David F.; Mueller, Maria F.; Aiguabella, Nuria; Klare, Hendrik F. T.; Oestreich, Martin
Abstract An efficient protocol for the base‐free dehydrogenative Si‐N coupling of monohydrosilanes with weakly to moderately nucleophilic NH‐groups is described.